John Fiske's Semiotic Analysis: Representation of Hasan Sabbah's Religious Political Movement in the Seljuk Awakening Series - Ika Sanger (Jurnal Komunikasi Islam dan Kehumasan (JKPI), 2023)
Representation could be said to work for, produce, naturalize, and stabilize a dominant meaning, but representation could also produce new meanings, or change meanings. The representations played in the Seljuk Revival series feature many religious political movements, which were more focused on one character who was highly highlighted in the Seljuk Revival Series, namely Hasan Sabbah. Researchers used the research method Reseach Library (Library Study), using descriptive techniques, sources obtained from books, articles, and Google Books. The results of this study could be seen from John Fiske's level of semiotic analysis; The reality level, which was focused on speech codes; which shows that Hasan still shows two different meanings of speech in different places, praising those who were considered enemies and saying no praise when behind the enemy. Representational Level, focused on characters and dialogue; the character code showed a person who was religious, and willing to sacrifice for his beliefs. the dialogue code showed him as a person who did not want to get involved with people who were not in line with the faith of the priesthood. Ideology level, could be seen in the serial picture shown that the ideology being played was religious political ideology and the Inner Ideology, namely Ta'wil al-Bathin, which served as the basis for the formation of Ismailiyah Nizar. however, inner ideology had always been considered heretical.